Effect of potato (Solanum tuberosum) meal on broiler production - Sakib, N; Sultana, F; Howlider, MAR; Rana, MS (Bangladesh Journal of Animal Science, 2014)
The study was conducted to find out the performance of broiler birds fed different levels of potato meal (PM). The levels of potato meal in the different treatment rations were control 0, 5, 10, and 15 g/kg, respectively. Dietary levels of PM did not affect live weight at 7, 21, 28, 35 and 42 days of age. However, live weight of broiler differed significantly (p<0.05) among different levels of PM in the diet at 14 days of age and increasing level of PM had a tendency to decrease live weight between 7 and 14 days of age. Feed intake increased linearly with the increasing level of dietary PM (p<0.05) up to 35 days of age followed by a decline at 42 days of age. At 14 days of age, feed intake in control diet and 10g PM diets were similar and intermediate, it was highest in 15g PM and lowest on 5g PM diet. However, feed intake did not differ (p>0.05) among different levels of PM in diet at 21, 28, 35, and 42 days of age. Feed conversion ratio (FCR) decreased between 7 and 14 days of age with the least conversion observed at 15 g/kg PM level. FCR didnt differ significantly (p<0.05) among different levels of PM in diet. Mortality did not alter due to the increasing levels of PM regardless of age of broiler. Dietary PM did not modify the dressing yield, breast meat, thigh meat and other carcass traits. Feed cost in different dietary PM groups were more or less similar, whereas total production cost per kg broiler were increased in 10 % Potato Meal than control (p<0.05). However, sale price (Taka/broiler) and sale price (Taka/kg broiler) were more or less similar in all treatments. Profit per broiler and per kg broiler were reduced as the PM level increased in the diet. It was therefore concluded that use of potato meal at 5 to 15g/kg diet may not be suitable for growth and profitability in broiler production. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21647 Bang. J. Anim. Sci. 2014. 43 (3): 192-196